The Function of Ammonia Oxidizers Community in the Environment - Ginawi, Amjed; Yan, Yunjun (PSM Microbiology, 2019)
This review summarizes the available data regarding the environments of ammonia oxidizers community, the adaptation of ammonia oxidizers communities to shift in the sediment, and denitrifying microbes. The advancements of molecular biology techniques have encouraged the fast recent developments in the sector. Various methods for implementing so are discussed. The function of ammonia oxidizers community and denitrifying microorganism composition was investigated through a high throughput of the 16S rRNA amplicon sequencing procedure. There is a potential need to observe the species-specific appearance of these microorganisms in each environment and determine the relative abundance of several kinds. More effort is required to isolate these microorganisms and determine their functions through biochemical, physiological and molecular techniques. However, the investigation with deoxyribonucleic acid (DNA), antibodies, and the polymerase chain reaction (PCR) was preferred mainly to report the composition of chemolithoautotrophic bacteria.